Textbook of physiotherapy for cardio-respiratory, cardiac surgery and thoracic surgery conditions - Madhuri, CB (New Delhi : Japee Brothers Medical Publishers, 2008)
Physiotherapy is ever advancing field. The recent advances have made physiotherapy important in every field. This title has been designed basically for the physiotherapy students and professionals of all the fields. Each topic is clearly explained with Anatomy ,Clinical significance and applied anatomy and the conditions are clearly explained in detail with physiotherapy intervention and if surgery required then pre and post operative physiotherapy management is explained.
1. Cardio-respiratiry system 2. Cardiac surgery 3. Thoracic surgery 4. Micellaneous 5. Physiotherapy rehabilitation programe
Texto en Inglés Index
Keywords: FISIOTERAPIA